1970
DOI: 10.1037/h0028525
|View full text |Cite
|
Sign up to set email alerts
|

Ability correlates in learning a psychomotor task.

Abstract: Factor analysis of a battery of psychomotor reference tests and learning performance replicated previous findings of both increasing and decreasing taskspecific factors in the acquisition of skill in a rotary pursuit task. A comparison of ability correlates of proficiency at various stages of practice for a group in which tracking speed was emphasized versus a group where accuracy was emphasized suggests that difference in method of approaching the task may be responsible for much of the task-specific factor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Although there were no significant differences among the validity coefficients for either the concurrent or predictive validity groups, the amount of shared variance between the work sample and criterion is higher than for the two paper and pencil tests in the concurrent group (nearly twice as great) and somewhat higher in the predictive group. This finding makes sense intuitively, and is consistent with the findings of Asher and Sciarrino (1974) and Hinrichs (1970) in that a predictor which most closely resembles the criterion task should account for greater variance than measures which don't have a point to point correspondence with the criterion. This result is also similar to the findings documented by Gordon and Kleiman (1976) who reported that a work sample was a better predictor of trainability than an aptitude test.…”
Section: Disscussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although there were no significant differences among the validity coefficients for either the concurrent or predictive validity groups, the amount of shared variance between the work sample and criterion is higher than for the two paper and pencil tests in the concurrent group (nearly twice as great) and somewhat higher in the predictive group. This finding makes sense intuitively, and is consistent with the findings of Asher and Sciarrino (1974) and Hinrichs (1970) in that a predictor which most closely resembles the criterion task should account for greater variance than measures which don't have a point to point correspondence with the criterion. This result is also similar to the findings documented by Gordon and Kleiman (1976) who reported that a work sample was a better predictor of trainability than an aptitude test.…”
Section: Disscussionsupporting
confidence: 84%
“…Previous research has demonstrated the utility of the behavioral consistency model in a variety of settings. For example, Hinrichs (1970) found that the best predictor of performance in a rotary pursuit task was a test which most closely resembled the criterion. In a review of work samples, Asher and Sciarrino (1974) concluded that complex tasks such as work samples, which are designed to be miniature replicas of the criterion, should be more powerful predictors than tests…”
Section: The Predictive Validity Of a Work Sample: A Laboratory Studymentioning
confidence: 99%
See 1 more Smart Citation
“…An important point to be made, however, is that, when applying a remediation or rehabilitation program based on this notion, success may be proportional to the extent to which the underlying subskills and the skill-to-be-improved are related. Early studies involving factor analysis (e.g., Fleishman & Bartlett, 1969;Guilford 1958;Seashore, Buxton, & McCollum, 1940) and, more recently, systematic task analysis (Hinricks, 1970;Jones, 1970) are examples of efforts to understand these relationships. The subsequent major works of Diller et al (1974) and Ben-Yishay, Rattok, and Diller (Note 1) are examples of a comprehensive approach that…”
Section: Copying Addressmentioning
confidence: 98%
“…A number of the studies included in Table 1 also contained additional data relevant to this issue of changes in predictive validities over time. These studies included Hinrichs (1970) , Hollander (1965), Humphreys (1968), Parker & Fleishman (1960), and Reynolds (1952). Hinrichs (1970) was a study of ability correlates of learning on a psychomotor rotary pursuit or tracking task.…”
Section: Omitted Studiesmentioning
confidence: 99%